Prarancangan Pabrik Etilen Dari Cracking Nafta Menggunakan Proses Maxene Dengan Disain Alat Utama Menara Absorbsi Wet Scrubber - Farhan Hidayatullah; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The design of an ethylene plant from cracking naphtha using the MaxEne process aims to assess the feasibility of the plant for establishment. The ethylene plant is designed with a capacity of 155,000 tons/year. Naphtha, which is the main raw material for obtaining products ethylene according to capacity and the production process used is MaxEne where The MaxEne unit is a new and innovative process for optimizing naphtha steam cracker operations and catalytic reform. The main product of ethylene is obtained through separation using a absorption tower wet scrubber with an operating condition of 60 oC at a pressure of 5 bar where the bottom product is H2S separated from cracked gas at top product which is including ethylene in it. This factory is planned to be established in 2023 near Pertamina RU II Dumai, Riau. Based on the results of economic analysis and factory feasibility, Cumulative Cash Ratio (CCR) is 2,2, a pay back period is 3,46 years and a rate of return on investment (ROROI) of 34,4% for non-discounted techniques. Based on the results of economic analysis, the pre-design of the ethylene plant with a capacity of 155,000 tons/year is feasible to consider its establishment. Keywords: Ethylene, Naphtha, MaxEne, Absorption Tower, Analysis Economic